2021
DOI: 10.1001/jamaoncol.2020.7857
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Metastatic Burden With Survival Benefit From Prostate Radiotherapy in Patients With Newly Diagnosed Metastatic Prostate Cancer

Abstract: This exploratory analysis of a randomized clinical trial evaluates the association of bone metastasis count and location with survival benefit from prostate radiotherapy in patients with newly diagnosed metastatic prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 24 publications
2
47
0
2
Order By: Relevance
“…These numbers are supported by other reports covering the same period for Danish and international cohorts [8][9][10][11][12][13]. Survival rates are likely to have improved since then [14][15][16], but bone metastasis remains an incurable condition. Contributing to the poor prognosis are the consequences of bone metastases such as anemia, increased susceptibility to infection, life-threatening hypercalcemia, spinal cord compression, severe pain, fatigue, increased risk of skeletal fractures, and decreased mobility [17][18][19][20].…”
Section: Introductionsupporting
confidence: 66%
“…These numbers are supported by other reports covering the same period for Danish and international cohorts [8][9][10][11][12][13]. Survival rates are likely to have improved since then [14][15][16], but bone metastasis remains an incurable condition. Contributing to the poor prognosis are the consequences of bone metastases such as anemia, increased susceptibility to infection, life-threatening hypercalcemia, spinal cord compression, severe pain, fatigue, increased risk of skeletal fractures, and decreased mobility [17][18][19][20].…”
Section: Introductionsupporting
confidence: 66%
“…Aa survival benefit was found in favor of primary prostate radiotherapy in men with ≤3 metastases (HR 0.68, 95% CI 0.52-0.90, p=0.0098). A secondary analysis of this trial demonstrated a significant survival benefit in patients with lymph node only metastases (HR 0.60, 95% CI 0.33-1.09) as well as a failure-free survival benefit beyond 4 bone metastases up to 8 bone metastases (93). Overall, these are encouraging results but need to be further evaluated prospectively, particularly with new imaging modalities.…”
Section: Advances In Radiotherapy Techniques Treatment Deliverymentioning
confidence: 81%
“…13 14 Randomised trials of patients with distant metastases of prostate cancer showed that additional radiation therapy to the primary lesion resulted in better overall survival and failure-free survival in patients with low metastatic burden. 15 However, patient selection in such cases with DTC has not been established. Brierley and Sherman advocated that patients with uncontrolled cervical lesions are good candidates for high-dose radiation therapy because these patients may survive longer, despite metastatic DTC.…”
Section: Discussionmentioning
confidence: 99%